Inflation Forecast Contracts - Hans Gersbach; Volker Hahn (ETH Zurich, CER-ETH - Center of Economic Research, 2011)
We introduce a new type of incentive contract for central bankers: inflation forecast contracts, which make central bankers' remunerations contingent on the precision of their inflation forecasts. We show that such contracts enable central bankers to influence inflation expectations more effectively, thus facilitating more successful stabilization of current inflation. Inflation forecast contracts improve the accuracy of inflation forecasts, but have adverse consequences for output. On balance, paying central bankers according to their forecasting performance improves welfare.
Keywords: E58; 330; central banks; incentive contracts; transparency; inflation targeting; inflation forecast targeting; intermediate targets; Inflationssteuerung; Inflationserwartung; Politische Kommunikation; Experten; Leistungsanreiz; Theorie